; Simplified =
Let "Zoe" = z
Let "Luke" = x
x = 16/2 + 3 is your equation
You're expression is
~
they are 2 similar triangles, one is smaller than the other. they are in the ratio of 2:1,
hence 7x =56÷2
7x=28
x=4
Answer:
The answer is A.
Step-by-step explanation:
Firstly, you have to take out the common terms for this expression. In this expression, the common terms ard 2 and m :
![2 {m}^{3} - 12 {m}^{2} + 18m](https://tex.z-dn.net/?f=2%20%7Bm%7D%5E%7B3%7D%20%20-%2012%20%7Bm%7D%5E%7B2%7D%20%20%2B%2018m)
![= 2( {m}^{3} - 6 {m}^{2} + 9m)](https://tex.z-dn.net/?f=%20%20%3D%202%28%20%7Bm%7D%5E%7B3%7D%20%20-%206%20%7Bm%7D%5E%7B2%7D%20%20%2B%209m%29)
![= 2m( {m}^{2} - 6m + 9)](https://tex.z-dn.net/?f=%20%3D%202m%28%20%7Bm%7D%5E%7B2%7D%20%20-%206m%20%2B%209%29)
Next you have to factorise the brackets :
![{m}^{2} - 6m + 9](https://tex.z-dn.net/?f=%20%7Bm%7D%5E%7B2%7D%20%20-%206m%20%2B%209)
![= {m}^{2} - 3m - 3m + 9](https://tex.z-dn.net/?f=%20%3D%20%20%7Bm%7D%5E%7B2%7D%20%20-%203m%20-%203m%20%2B%209)
![= m(m - 3) - 3(m - 3)](https://tex.z-dn.net/?f=%20%3D%20m%28m%20-%203%29%20-%203%28m%20-%203%29)
![= (m - 3)(m - 3)](https://tex.z-dn.net/?f=%20%3D%20%28m%20-%203%29%28m%20-%203%29)
![= {(m - 3)}^{2}](https://tex.z-dn.net/?f=%20%3D%20%20%7B%28m%20-%203%29%7D%5E%7B2%7D%20)
So the final answer is :
![2m {(m - 2)}^{2}](https://tex.z-dn.net/?f=2m%20%7B%28m%20-%202%29%7D%5E%7B2%7D%20)
Answer:
Question 2: Radios remaining is the dependent variables and the hours are the Independent variables
We have to find the values of F.
In this case. F is unlikely to be a polynomial.
But the problem is, we can’t calculate the values of F directly.
There is no real value of x for which x = x−1 x because F isn’t defined at 0 or 1. so,
substituting x = 2.
F(2) + F(1/2) = 3.
Substitute, x = 1/2
F(1/2) + F(−1) = −1/2.
We still are not getting the required value,
therefore,
Substitute x = −1
As, F(2) +F(−1) = 0.
now we have three equations in three unknowns, which we can solve.
It turns out that:
F(2) = 3/4
F(3) = 17/12
F(4) = 47/24
and
F(5) = 99/40
Setting
g(x) = 1 − 1/x
and using
2 → 1/2
to denote
g(2) = 1/2
we see that :
x → 1 - 1/x → 1/(1-x) →xso that:
g(g(g(x))) = x.
Therefore, whatever x 6= 0, 1 we start with, we will always get three equations in the three “unknowns” F(x), F(g(x)) and F(g(g(x))).
Now solve these equations to get a formula for F(x)
As,
h(x) = (1+x)/(1−x)which satisfies
h(h(h(h(x)))) = xNow, mapping x to h(x) corresponds to rotating the circle by ninety degrees.